Passive microwave atmospheric measurements - Part I : Absorption of microwaves by atmospheric gases-Oxygen and water vapour (MAUSAM, 1980)
The expression for absorption coefficient for microwave frequencies which is required in the inversion of radiative transfer equation is described in terms of meteorological parameters. Computational scheme has been developed and the results obtained for a standard tropical atmosphere for 19.35 GHz and 22.235 GHz, the frequencies used in satellite microwave radiometer onboard the second Indian satellite Bhaskara Relative contribution to the absorption coefficients for frequencies from 10 GHz to 70 GHz is also described for surface meteorological parameters. The algorithm and subroutine package may as well be used for interpreting any microwave radiometric data for meteorological and oceanographic studies.